Antitumour activity of the glycoengineered type II anti‐CD20 antibody obinutuzumab (GA101) in combination with the MDM2‐selective antagonist idasanutlin (RG7388). (18th April 2016) - Herting, Frank; Herter, Sylvia; Friess, Thomas; Muth, Gunther; Bacac, Marina; Sulcova, Jitka; Umana, Pablo; Dangl, Markus; Klein, Christian
Abstract: Objectives: To investigate whether the glycoengineered type II anti‐CD20 monoclonal antibody obinutuzumab (GA101) combined with the selective MDM2 antagonist idasanutlin (RG7388) offers superior efficacy to monotherapy in treating B‐lymphoid malignancies in preclinical models. Methods: The combined effect of obinutuzumab or rituximab plus idasanutlin on direct cell death/apoptosis induction and antibody‐dependent cellular cytotoxicity (ADCC) was evaluated using p53 wild‐type Z‐138 and DoHH‐2 lymphoma cells. Furthermore, whole blood B‐cell depletion was analysed, and tumour growth inhibition was evaluated in subcutaneous xenograft models. Results: Idasanutlin induced concentration‐dependent death of Z‐138 and DoHH‐2 cells. At concentrations >10–100 nm, idasanutlin enhanced obinutuzumab‐induced death of DoHH‐2 and Z‐138 cells without negatively impacting obinutuzumab‐mediated ADCC, natural killer cell activation or whole blood B‐cell depletion. In the Z‐138 xenograft model, a suboptimal dose of obinutuzumab with idasanutlin yielded substantial tumour growth inhibition and prolonged survival in a time‐to‐event analysis. In the DoHH‐2 model, idasanutlin plus obinutuzumab showed superior tumour growth inhibition to idasanutlin plus rituximab. Conclusions: Obinutuzumab plus idasanutlin enhanced cell death of p53 wild‐type tumour cells vs. rituximab plus idasanutlin without affecting obinutuzumab‐mediated ADCC or B‐cell depletion and showed robust antitumour efficacy in xenograft models, strongly supporting the investigation of this combination in clinical trials.